Modelling and Laboratory Studies on the Adhesion Fatigue Performance for Thin-Film Asphalt and Aggregate System - Dongsheng Wang; Junyan Yi; Decheng Feng (The Scientific World Journal)
Adhesion between asphalt and aggregate plays an important role in the performance of asphalt mixtures. A low-frequency adhesion fatigue test was proposed in this paper to study the effect of environment on the asphalt-aggregate adhesion system. The stress-based fatigue model had been utilized to describe the fatigue behavior of thin-film asphalt and aggregate system. The factors influencing the adhesion fatigue performance were also investigated. Experiment results show that asphalt has more important effect on the adhesion performance comparing with aggregate. Basalt, which is regarded as hydrophobic aggregates with low silica content, has better adhesion performance to asphalt binder when compared with granite. The effects of aging on the adhesion fatigue performance are different for PG64-22 and rubber asphalt. Long-term aging is found to reduce the adhesion fatigue lives for rubber asphalt and aggregate system, while the effect of long-term aging for aggregate and PG64-22 binder system is positive. Generally the increased stress amplitude and test temperature could induce greater damage and lead to less fatigue lives for adhesion test system.